The effectiveness of EM4 addition in the biofilter to reduce nitrate and phosphate concentration in the palm oil industry liquid waste - Saputra, Ariadi; Harahap, Sampe; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Palm oil industrial liquid waste is rich in Nitrate and Phosphate and thus need to be processed before being flown to environment. A study aims to reduce the nitrate and phosphate in that waste by using a biofilter that was added with EM4 has been conducted in April-May 2019. There were 3 treatments applied, namely the addition of 0.12 ml/L, 0.15 ml/L and 0.18 ml/L EM4 in the anaerob and aerob tanks, 3 replications. The waste was settled for 3 days in the anaerob tank and 3 days in the aerob tank. The treated waste was then tested for Nitrate and Phosphate concentration. The treated waste was also used for rearing Cyprinus carpio seedlings. Results shown that after being treated using the EM4 enriched biofilter, the nitrate reduced into 6.4226mg/L and that of the phosphate was reduced into 0.3673 mg/L. The best treatment to reduce the Nitrate and Phosphate concentration was the addition of 0.15 ml/L EM4in the biofilter. The survival of C. carpioseedling reared in the treated waste was 93.33%. It can be concluded that the addition of EM4 to the biofilter tank was able to reduce the Nitrate and Phosphate concentration in the palm oil industrial liquid waste Keywords : Effective Microorganism-4, Cyprinus carpio, Aerob tank, Anaerob tank